Clozapine-induced hypertension: A paradox - Hamza Hussain; P. C. B. Gupta; Rajeevi Keeta (Telangana Journal of Psychiatry)
Clozapine is a second-generation antipsychotic agent, considered the drug of choice for treatment-resistant schizophrenia. While tachycardia and postural hypotension are common cardiovascular side effects, reports of new-onset persistently elevated blood pressure are rare. We present a case where clozapine initiation led to hypertension requiring pharmacological intervention. A 42-year-old female with no prior hypertension and normal baseline blood pressure developed high blood pressure (150/90 mmHg) on clozapine 50 mg/day. These findings were consistent on subsequent trials, necessitating the continuation of amlodipine alongside clozapine at a 100 mg dose to maintain blood pressure control.